2022
DOI: 10.3390/sym14081496
|View full text |Cite
|
Sign up to set email alerts
|

The Novelty of Thermo-Diffusion and Diffusion-Thermo, Slip, Temperature and Concentration Boundary Conditions on Magneto–Chemically Reactive Fluid Flow Past a Vertical Plate with Radiation

Abstract: The significance of radiation, Soret and Dufour’s effects on MHD flow in a porous media near a stagnation point past a vertical plate with slip, temperature, and concentration boundary conditions were investigated. Local similarity variables are used in the solution, which reduces the PDEs into analogous boundary value problem for ODEs. Symmetry analysis can be used to detect these variations in local similarity. To numerically explain the problem, a shooting approach and the MATLAB bvp4c solver are utilized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Most researchers are focused on this type of area because there are lots of applications in this field. So I have taken the literature from Lakshmi Devi [1] and Khan [2] to motivate this research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers are focused on this type of area because there are lots of applications in this field. So I have taken the literature from Lakshmi Devi [1] and Khan [2] to motivate this research.…”
Section: Introductionmentioning
confidence: 99%
“…The important effects are geosciences and chemical engineering. Niranjan et al [11] and Lakshmi Devi et al [1] discussed numerically the effects of Rd and chemical reactions on MHD flow in a porous medium incorporating diffusion-thermo and thermo-diffusion effects. Convective heat exchange simulation of viscous fluid flow with heat radiation and slip effects is examined numerically by Ullah et al [12] along a vertically symmetric warmed plate submerged in a porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the chemical reaction parameter increases in the case of generation but decreases in the case of destruction. Hayat et al [3] and Lakshmi Devi et al [4] investigated over a strecting sheet in an MHD flow with the effects of chemical reaction and radiation in a porus medium near a stagnation point.…”
Section: Introductionmentioning
confidence: 99%